The reproducibility of blood-born and psychological markers of fatigue and recovery in elite athletes - Fullagar, H.; Hecksteden, A.; Julian, R.; Skorski, S.; Hammes, D.; Meyer, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: There is a lack of consensus regarding the best markers to monitor fatigue in athletes (Meeusen et al., 2013), especially since little is known about the intraindividual variability of potential parameters and their responses. From both a practical and theoretical point of view this would be worth knowing to enable interpretation of fatigue markers as a result of changes in fatigue status or random variation. Thus, the aim of this study was to determine the reproducibility of blood and psychological fatigue markers in elite junior athletes during endurance training. Methods: Twenty-two (16 M, 6 F; 177.6cm±6.5; 67kg±9.3; 18.2y±3.2) tri-athletes and swimmers (regional to national level) completed 5 weeks of low-intensity/high volume endurance training which was constant over the study. Venous blood samples (VBS) and psychological questionnaires (Hitzschke et al., 2013; Acute Stress and Recovery Scale (ASRS) comprising of scales each with 0-6 weighting (6=fully recovered) of perceptual fatigue were collected every Monday (MON; following recovery/no training 24h prior) and Friday (FRI; following a week of 10-12 training sessions) prior to training at the same time of day. VBS were analysed immediately for creatine kinase (CK) and urea (U) using appropriate laboratory procedures. Means, standard deviations and coefficients of variation (CV) were calculated for ASRS and for MON, FRI and difference between MON and FRI (DIFF) for CK and U. Results: Mean CK for MON was 220.1±154.5 with a CV 40.0%. Mean CK for FRI was 266.0±141.5 with a CV 34.2%. Mean DIFF for CK was 53.9±153.1 (p<0.05) with a CV of 219.7%. Mean U for MON was 32.0±8.7 with a CV 18.5%. Mean U for FRI was 34.3±8.8 with a CV 21.9%. Mean DIFF for U was 2.1± 9.9 (p<0.05) with a CV 73.0%. Mean scores for ASRS ranged from 1.94-4.01 and a CV range on MON of 18.9-51.9% and 17.8-50.2% for FRI. Discussion: Our results suggest the reproducibility of raw values and training induced changes in these indicators of fatigue is low. This impedes the diagnostic accuracy of detecting changes in the fatigue status of elite athletes. However, training induced changes in the current study were small. It could be speculated that larger changes would result in better reproducibility. Since this study only used two blood markers, this supports current recommendations to use a larger array of parameters in future research (Le Meur et al., 2013).